Assessment of urine CCL2 as a potential diagnostic biomarker for acute kidney injury and septic acute kidney injury in intensive care unit patients - Yuan Peng; Qin Wang; Fang Jin; Tao Tao; Qihong Qin (Renal Failure)
Acute kidney injury (AKI) is a prevalent and serious condition in the intensive care unit (ICU), associated with significant morbidity and mortality. Septic acute kidney injury (SAKI) contributes substantially to AKI cases in the ICU. However, current diagnostic methods have limitations, necessitating the exploration of novel biomarkers. In this study, we investigated the potential of plasma and urine CCL2 levels as diagnostic markers for AKI and SAKI in 216 ICU patients. Our findings revealed significant differences in plasma (p < 0.01) and urine CCL2 (p < 0.0001) levels between AKI and non-AKI patients in the ICU. Notably, urine CCL2 demonstrated promising predictive value for AKI, exhibiting high specificity and sensitivity (AUC = 0.8976; p < 0.0001). Furthermore, we observed higher urine CCL2 levels in SAKI compared to non-septic AKI (p < 0.001) and urine CCL2 could also differentiate SAKI from non-septic AKI (AUC = 0.7597; p < 0.0001). These results suggest that urine CCL2 levels hold promise as early biomarkers for AKI and SAKI, offering valuable insights for timely intervention and improved management of ICU patients.